Analisis Pengaruh Emotional Attachment, Dan Experiential Value Terhadap Loyalitas - Silvia Ekasari; Lalang Saksono; Elizabeth Elizabeth; Musran Munizu; Sonny Santosa (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study analyzes the influence of Emotional Attachment and Experiential Value on Sharia Customer Loyalty in the Indonesian Islamic banking industry. The study employed a quantitative approach using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The sample consisted of 325 active customers of Islamic banks selected using a purposive sampling technique. Data collection was conducted through a five-point Likert-scale questionnaire. Data analysis was performed using SmartPLS 4 through outer and inner model testing, including validity, reliability, R-square, Q-square, effect size, bootstrapping, and hypothesis testing. The results indicate that Emotional Attachment and Experiential Value have a positive effect on Sharia Customer Loyalty. This research provides a theoretical contribution to the development of customer engagement based on Islamic values ​​and offers practical implications for Islamic banks in enhancing customer loyalty through Islamic services, emotional connections, and quality service experiences.